Pendekatan Holistik Untuk Pencegahan Bullying: Edukasi Dan Psikososial di SAM Tengku Ampuan Jemaah Sungai Besar Malaysia - Edy Muslimin; Meti Fatimah; Muh. Nur Rochim Maksum; Aulia Rachma Fajria; Agit Purwo Hartanto; Riski Kristianto Pambudi; Ridwan Rohmad Yunadi; Arilana Nur ‘Izi (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: Bullying in Malaysian secondary schools is a serious issue with the prevalence of cases continuing to increase and adversely affecting the mental health of adolescents. At SAM Tengku Ampuan Jemaah Selangor, Malaysia it was found that more than 30% of stu-dents still consider bullying to be a normal social dynamic. This service aims to raise awareness of the dangers of bullying, equip school residents with social-emotional skills, and create a safe and inclusive school environment. The method used in the PkM-International Partnership uses a holistic approach that combines anti-bullying education and psychosocial reinforcement for four days for 219 students. The implementation strategy includes interactive workshops, case discussions, role-play simulations, and educational poster creation. The results of the service showed a significant increase in participants' understanding with an increase in the average score from 2.99 to 3.74 (25.10%). The real impact of this activity is the strengthening of anti-bullying literacy and the formation of a more responsive internal school mechanism to build a school cul-ture that is free of violence and compassion. Keywords: bullying; awareness; school environment; holistic approach; students Abstrak: Perundungan di sekolah menengah Malaysia merupakan isu serius dengan prevalensi kasus yang terus meningkat dan berdampak buruk pada kesehatan mental remaja. Di SAM Tengku Ampuan Jemaah Selangor, Malaysia ditemukan bahwa lebih dari 30% siswa masih menganggap perundungan sebagai dinamika sosial yang wajar. Pengabdian ini bertujuan untuk meningkatkan kesadaran akan bahaya perundungan, membekali warga sekolah dengan keterampilan sosial-emosional, serta menciptakan lingkungan sekolah yang aman dan inklusif. Metode yang digunakan dalam PkM-Kemitraan Internasional ini menggunakan pendekatan holistik yang memadukan edukasi anti-bullying dan penguatan psikososial selama empat hari terhadap 219 peserta didik. Strategi pelaksanaan mencakup workshop interaktif, diskusi kasus, simulasi role-play, dan pembuatan poster edukasi. Hasil pengabdian menunjukkan peningkatan signifikan pemahaman peserta dengan kenaikan skor rata-rata dari 2,99 menjadi 3,74 (25,10%). Dampak nyata dari kegiatan ini adalah penguatan literasi anti-bullying serta terbentuknya mekanisme internal sekolah yang lebih responsif guna membangun budaya sekolah yang bebas kekerasan dan penuh kasih sayang. Kata kunci: bullying; kesadaran; lingkungan sekolah; pendekatan holistik; peserta didik